Computational modeling of the cabin interior of the conceptual model of amphibian aircraft "Lapwing". (December 2017) - Abbasov, Iftikhar B.; Orekhov, V'iacheslav V.
Highlights: This paper examines issues regarding computational modeling of the cabin interior of the conceptual model of amphibian aircraft "Lapwing". Objects interior is designed on the basis of ergonomic principles. The stages of modeling a comfortable passenger seat from a sketch to a finished model are described in detail. For cabin of different variant, the scenes of realistic rendering are introduced. Abstract: The article is concerned with computer modeling of the cabin interior of the conceptual model of the amphibian aircraft "Lapwing". Various concepts of the passenger compartment layout discussed. Designing of interior objects is carried out taking into account ergonomic norms. The stages of modeling a comfortable passenger seat from a sketch to a finished model are described in detail. The method of extruding polygons is used for modeling the interior objects. When shading a scene, the materials are assigned at the sub-object level. The final scenes of a realistic rendering of the cabin interior of amphibian aircraft are shown.